ATP regulates the phosphorylation and degradation of myofibrillar proteins in ground ovine muscle - Chi REN; Cheng-li HOU; De-quan ZHANG; Xin LI; Xiong XIAO; Yu-qiang BAI (Journal of Integrative Agriculture)
Phosphorylation post-translational modification plays an important role in postmortem muscle quality traits. Adenosine triphosphate (ATP) is an energy source and a key substrate of phosphorylation which provides the phosphatase groups to proteins in the presence of protein kinases. However, in postmortem muscle, the effects of ATP content on phosphorylation are poorly studied. The study investigated the effect of ATP on protein phosphorylation and degradation in postmortem ovine muscle. The ground muscle with/without additional ATP were treated/control groups and stored at 25 and 4°C, respectively. The ATP content led to different changes of pH value between the ATP-treated and control groups. The phosphorylation level of myofibrillar proteins was higher (P<0.05) in ATP-treated group compared to the control group at both temperatures, which suggested that ATP played a vital role in postmortem protein phosphorylation. A slower degradation rate of µ-calpain, desmin and troponin T was observed in the ATP-treated group which showed that there was a negative relationship between ATP level and the degradation of proteins. These observations clearly highlighted the role of ATP on the development of meat quality by regulating the phosphorylation and degradation of myofibrillar proteins in postmortem ovine muscle.